An Object Oriented Model of a Railway Safety-Related Control System - Rastocny, Karol; Zahradnik, Jiri; Janota, Ales (Communications - Scientific letters of the University of Zilina, 2002)
There is a variety of methods and formalisms usable for writing specifications of railway interlocking and signalling systems or their subsystems. To write a consistent technical specification means to make a model with a required level of precision, clarity and economy of expression that is free of unknown spots and/or conflicts. One of possible formalisms suitable for making such models seems to be the Unified Modeling Language’ (trademark of OMG). The paper presents experience and knowledge of authors who have worked over transcription of informal specification of a new railway interlocking and signalling system into the UML based object-oriented model. The main attention is paid to analysis and design phases. The former phase results in use case diagrams and sequential diagrams, the latter in class/object diagrams and statechart diagrams. The syntax of the discussed diagrams is in accordance with the UML ver. 1.2 as given by the software tool Rhapsody’ ver. 2.2 (a trademark of I-Logix). Experiences and advantages resulting from the presented approach are summarised within conclusions.